Effect of Excess Dietary Methionine on the Performance of Laying Hens of Various Live Body Weight - Çadırcı, Şahin; Özbakır, Gonca Özmen; Kiraz, Ayfer Bozkurt (Turkish Journal of Agriculture - Food Science and Technology, 2015)
An experiment was conducted with laying hens to determine the effects of feeding excesses of methionine in a practical layer diet. One hundred and thirty two laying hens at 61 weeks of age were used for the experiment. Two body weight groups (light and heavy) and three levels of mehionine were assigned to six groups of laying hen in a 2x3 factorial design. The diets were a 16.5% crude protein corn and soybean meal positive control diet (0.33% methionine), and this diet fortified with 1.00% additional DL-Methionine or 1.50% additional DL-Methionine. The diets were fed ad libitum to the hens for 10 consecutive weeks of production. For the total production period, body weight gain, hen-day egg production, egg weight, egg mass, daily feed intake and feed conversion ratio were not significantly different among any of the treatments in the two body weight groups (P>0.05). The study indicated that considerable tolerance exists in laying hens for individual excesses of the DL-Methionine commonly used as supplement in poultry diets.